Norepinephrine and dopamine increase motility, biofilm formation, and virulence of Vibrio harveyi - Yang, Qian; Anh, Nguyen D. Q.; Bossier, Peter; Defoirdt, Tom (Frontiers in Microbiology, 2014)
Vibrio harveyi is one of the major pathogens of aquatic organisms, affecting both vertebrates and invertebrates, and causes important losses in the aquaculture industry. In order to develop novel methods to control disease caused by this pathogen, we need to obtain a better understanding of pathogenicity mechanisms. Sensing of catecholamines increases both growth and production of virulence-related factors in pathogens of terrestrial animals and humans. However, at this moment, knowledge on the impact of catecholamines on the virulence of pathogens of aquatic organisms is lacking. In the present study, we report that in V. harveyi, norepinephrine and dopamine increased growth in serum-supplemented medium, siderophore production, swimming motility and expression of genes involved in flagellar motility, biofilm formation, and exopolysaccharide production. Consistent with this, pretreatment of V. harveyi with catecholamines prior to inoculation into the rearing water resulted in significantly decreased survival of gnotobiotic brine shrimp larvae, when compared to larvae challenged with untreated V. harveyi. Further, norepinephrine-induced effects could be neutralized by α-adrenergic antagonists or by the bacterial catecholamine receptor antagonist LED209, but not by β-adrenergic or dopaminergic antagonists. Dopamine-induced effects could be neutralized by dopaminergic antagonists or LED209, but not by adrenergic antagonists. Together, our results indicate that catecholamine sensing increases the success of transmission of V. harveyi and that interfering with catecholamine sensing might be an interesting strategy to control vibriosis in aquaculture. We hypothesise that upon tissue and/or hemocyte damage during infection, pathogens come into contact with elevated catecholamine levels, and that this stimulates the expression of virulence factors that are required to colonize a new host.